Filsafat Dalam Manajemen Organisasi - Ahmad mu’adz hazmy sastria; Lailil maqnin; Mohammad rohman tio vandi; Rifqi lazuardian (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Philosophy is a science that is the subject and base of all knowledge and studies the truth, the true nature of nature, god, and man. An organization needs good management in order to run properly and achieve organizational goals. The purpose of this study is to determine the role of philosophy in organizational management. This research uses library research by collecting data through books, journals and research that has been done. The results of this study discuss the role of philosophy in organizational management. Philosophy is a way of achieving wisdom systematically and methodically. Management philosophy provides beneficial thinking and action in management and helps to its dynamic and challenging nature. Philosophy plays an important role in organizational management because it helps in the understanding of the nature of management, as well as the principles applied in administrative processes and managerial thinking.